Laparoscopic Totally Extraperitoneal Repair of Inguinal Hernia: A Series of 70 Repairs - Hossain, GM Zakir; Hasan, Rashedul; Rahman, Mofizur; Shahajahan, Md (Journal of Chittagong Medical College Teachers’ Association, 2010)
Key words: laparoscopic; total extraperitoneal; inguinal hernia DOI: 10.3329/jcmcta.v20i1.4931 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):27-30